ANALYSIS OF SOCIAL AND ECONOMIC CHANGES IN COMMUNITY OF POMPONG DRIVER AFTER THE CONSTRUCTION OF THE PATEMBO BRIDGE’S IN THE VILLAGE JAWI-JAWI SEI KEPAYANG SUB-DISTRICT WEST DISTRICT ASAHAN NORTHERN SUMATERA - Florensia Rajagukguk; Lamun Bathara; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The Patembo Bridge is the longest bridge in North Sumatra, which is 860 meters long and and 6 meters wide, the bridge was built in 1995 and the completion was completed in 2008. Research method is survey method that is by direct observation and structured interview, with qualitative data analysis that is t- Paired test.Patembo Bridge development caused changes to the social and economic of coastal communities, especially the former pompong drivers, the coast in general bridge construction has a positive impact but for the former driver of pompong bridge has a negative impact. The construction of the bridge has a positive impact on the general public because with the bridges the traffic access becomes smooth and reducing the expenses, especially the cost of crossing the river, so it is very helpful to the community, inversely with the former people of the pompong driver. The bridge construction has a negative impact because after the bridge construction they have to switch livelihood which resulted in lower revenue. In essence, bridge development causes social change for pompong driver’s society that is negative change, such as attitude change, habits and behavior change, education, and economic change that is change of livelihood, decreasing income change.Keywords: Patembo Bridge Building, Social Change, Economic Change, Former Pompong Driver Community.